Literature Review Persepsi Guru IPA SMP Terhadap Implementasi Strategi Pembelajaran Berdiferensiasi Pada Kurikulum Merdeka - Ni Putu Winni Widiastuti; I Wayan Redhana; I Wayan Suja; I Nyoman Tika (Postgraduate, University of Mataram, 2025)
Teacher competence in managing classroom learning through differentiation will also affect students' perceptions of the effectiveness of science learning that has been implemented. However, not all educators can implement differentiation learning techniques well. Many teachers also prefer to use the same teaching method for all students without considering their individual differences. This study aims to describe teachers' perceptions of the implementation of differentiated instruction strategies and analyze the opportunities for their application in science learning within the Merdeka Curriculum. The method used is a systematic literature review with PRISMA analysis of 10 relevant articles. The results show that teachers have a positive perception of differentiated instruction, recognizing the importance of addressing students' individual needs to create a conducive classroom environment. Differentiation strategies based on local strengths have been proven to enhance content, context, and product aspects of science literacy. Prior to implementation, students' science literacy was classified as very low in content (12.78%) and context/product (28.75%), and moderate in process (68.20%). After implementation, content increased to 70.62% (good), context or product to 43.87% (low), and science process skills to 77.18% (good). The main challenges include limited teacher competence and inadequate facilities, which must be addressed through continuous training and the use of technology.